2021
DOI: 10.1101/2021.04.04.21254906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a nighttime curfew on overnight mobility

Abstract: Background: Among non-pharmaceutical interventions, individual movement restrictions have been among the most impactful methods for controlling COVID-19 case growth. While nighttime curfews to control COVID-19 case growth have been implemented in certain regions and cities, few studies have examined their impacts on mobility or COVID-19 incidence. In the second wave of COVID-19, Canada's two largest and adjacent provinces implemented lockdown restrictions with (Quebec) and without (Ontario) a nighttime curfew,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
(6 reference statements)
3
5
0
Order By: Relevance
“…could not be evaluated separately and were therefore collapsed into broader categories (lockdowns, reopenings and moderate restrictions). Interestingly, overnight curfews considerably reduced SARS-CoV-2 transmission, corroborating results obtained in French Guiana (up to 35% reduction in transmission rates) [ 27 ] and in Quebec, Canada (similar reductions in human mobility) [ 28 ]. Moreover, we found that curfews starting earlier in the evening (6/7 pm) had a larger impact on transmission than curfews starting later (8/9 pm).…”
Section: Discussionsupporting
confidence: 77%
“…could not be evaluated separately and were therefore collapsed into broader categories (lockdowns, reopenings and moderate restrictions). Interestingly, overnight curfews considerably reduced SARS-CoV-2 transmission, corroborating results obtained in French Guiana (up to 35% reduction in transmission rates) [ 27 ] and in Quebec, Canada (similar reductions in human mobility) [ 28 ]. Moreover, we found that curfews starting earlier in the evening (6/7 pm) had a larger impact on transmission than curfews starting later (8/9 pm).…”
Section: Discussionsupporting
confidence: 77%
“…The mobility matrix between patches was derived using private data on geolocation service usage among a sample of approximately 2% of mobile devices in Ontario [14] during January–December 2020. Appendix A.3 details the specific methods and assumptions used; to summarize: Each devices was assigned an approximate home location (152.9 m 152.4 m) based on the most common location during overnight hours for each calendar month.…”
Section: Examplementioning
confidence: 99%
“…Following through Eqs. (11)(12), we obtain X h gag ′ a ′ y , representing the total contacts formed within home pools. Then, the total type y contacts formed between populations P ga and P g ′ a ′ across all relevant mixing pools is given by the sum:…”
Section: Mobility-related Mixingmentioning
confidence: 99%
“…The mobility matrix B gg ′ between patches was derived using private data on geolocation service usage among a sample of approximately 2% of mobile devices in Ontario [12] during January-December 2020. Appendix A.3 details the specific methods and assumptions used; to summarize: Each devices was assigned an approximate home location (152.9 m × 152.4 m) based on the most common location during overnight hours for each calendar month.…”
Section: Northern Ontariomentioning
confidence: 99%
See 1 more Smart Citation